Body composition and nutritional status in malignant pleural mesothelioma: implications for activity levels and quality of life. - Jeffery, E.; Lee, Y.C.G.; Newton, R.; Lyons-Wall, P.; McVeigh, Joanne; Nowak, A.; Cheah, H.; Nguyen, B.; Fitzgerald, D.; Creaney, J.; Straker, Leon; Peddle-McIntyre, C. (2019)
BACKGROUND/OBJECTIVES: Malignant pleural mesothelioma (MPM) is an incurable cancer and optimizing daily physical activity and quality of life are key goals of patient management. Little is known about the prevalence of pre-sarcopenia and malnutrition in MPM or their associations with patient outcomes. This study aimed to determine the prevalence of pre-sarcopenia and malnutrition in MPM and investigate if activity levels and quality of life differed according to body composition and nutritional status. SUBJECTS/METHODS: Patients with a diagnosis of MPM were recruited. Pre-sarcopenia was defined as low appendicular skeletal muscle mass (≤ 7.26 kg/m2 for men and ≤ 5.45 kg/m2 for women), measured by dual energy X-ray absorptiometry. Malnutrition was defined as a rating of B or C on the Patient-Generated Subjective Global Assessment. Outcome measures included objective activity levels (Actigraph GT3X) and health-related quality of life (HRQoL; Functional Assessment of Cancer Therapy General). RESULTS: Sixty-one people participated (79% male, median age 69 [IQR 62-74] years and median BMI 25.8 [IQR 24.3-28.4] kg/m2). Fifty-four percent were pre-sarcopenic and 38% were malnourished. Percent of time spent in light activity/day was lower in participants with pre-sarcopenia compared with non-sarcopenic participants (median 25.4 [IQR 19.8-32.1]% vs. 32.3 [27.1-35.6]%; p = 0.008). Participants with malnutrition had poorer HRQoL than well-nourished participants (mean 69.0 (16.3) vs. 84.4 (13.3); p < 0.001). CONCLUSION: Participants with MPM had high rates of pre-sarcopenia and malnutrition. Pre-sarcopenia was associated with poorer activity levels, whilst malnutrition was associated with poorer quality of life. Interventions that aim to address reduced muscle mass and weight loss, should be tested in MPM to assess their impact on patient outcomes.